PENGARUH MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP HASIL BELAJAR MATEMATIKA PADA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Alif Kurniadi Hilaby; Fatkhur Rohman; Fadhilah Khairani; Frida Destini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study addresses the issue of low learning outcomes among fourth-grade students in mathematics at SD Negeri 8 Metro Timur. The purpose of this research is to examine the effect of the Realistic Mathematics Education (RME) learning model on students' mathematics learning outcomes. This research employed a quantitative approach using a Quasi-Experimental Design, specifically the Non-Equivalent Control Group Design. The sample consisted of 57 students determined through saturated sampling. Data were collected using both test and non-test techniques and analyzed using simple linear regression analysis. The results indicated that the Realistic Mathematics Education learning model has a significant effect on the mathematics learning outcomes of fourth-grade elementary school students.